Utilization of institutional delivery services and its associated factor among mothers having children below 2 years in Dhangadimai municipality, Sirha district. - Singh,Sandeep (2019)
ABSTRACT: Background: Women giving birth to child in the facilities like hospitals with trained health care professionals etc. are institutional delivery. Utilization of institutional delivery is often promoted for reducing maternal morbidity and mortality. The main objective of the study was to assess the utilization of institutional delivery service and its associated factors among the mothers having children below 2 years. Methodology: A cross-sectional descriptive study was done using complete enumerative sampling method. Based on Z2PQ/D2, 165 mothers of reproductive age, having a child below 2 years in Dhangadimai Municipality-8 were taken as sample size. Semi-structured questionnaire were used as tools to collect the data. Analysis was done by IBM SPSS 23rd version. Association was analyzed by calculating chisquare. Result: The study found that 41.4% of the respondents had four or more ANC visit. The respondents going for institutional delivery was found to be 67.3% where proportion of home delivery was 32.7%. Among 22.4% of respondent who had visited health institution for PNC check-up, 54.1% of respondent had three times visit for PNC check-up. Parity (p-value= 0.02), maternal education (p-value < 0.001) number of ANC visit (p-value < 0.001) and means of transportation (p-value < 0.001) are the major factors associated with the utilization of institutional delivery services. Conclusion: From findings of the study; the practice of ANC Visit according to protocol was found to be poor. The practice of institutional delivery was found to be not satisfactory as the percentage of home delivery was higher. However, the rate of PNC visit was found to be not satisfactory as more than one-third of the respondents did not preferred for PNC visit due to several reasons. Parity, maternal education, ANC visit and means of transportation are the major factors associated with the utilization of institutional delivery services. Keywords: Maternal health, ANC, Institutional delivery, PNC.